INFLUENCE OF COLLABORATIVE PLANNING ON PERFORMANCE OF PHARMACEUTICAL FIRMS IN KENYA - Kiriinya, Akwalu Ezekiel; Ngugi, Dr. P. Karanja; Mwangangi, Dr. Patrick; Odhiambo, Prof. Romanus (International Journal of Supply Chain Management, 2018)
later